Modelling housing prices and credit activity - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2012)
Together, the housing and banking sectors of any capitalist nation can play an important hand in determining its overall economic health. This is clear from studies of booms and busts in the United States over this past decade and in Japan about three decades ago. A new econometric model now attempts to make sense of large changes in housing prices with corresponding changes in credit volume. The model was presented at a research seminar organised by SMU's School of Economics.